MANAGEMENT OF EMERGENCY ORAL SURGERY IN PREGNANCY - Alina Mihaela Elisei; Iulian Constantin; Patru Radu Stanciu; Anca Maria Fratila; Dragos Stanciu; Doriana Agop Forna; Alina Mihaela Calin (Romanian Society of Oral Rehabilitation, 2024)
This study addresses the management of emergency oral surgery during pregnancy, with a special focus on the safety and effectiveness of interventions in this sensitive context. The analysis focuses on identifying best practices and protocols to ensure the protection of both maternal and fetal health. Pregnancy trimesters are examined in detail to determine the optimal times and risks associated with surgery. The judicious use of anesthetics and drugs is also discussed, emphasizing the importance of choosing safe ones for use during pregnancy. Particular attention is paid to X-rays in the dental context, highlighting the need for radiation protection and the prudent use of this technology. The study also proposes patient management strategies, such as planning non-urgent treatments in the second trimester, interdisciplinary consultation, and continuous monitoring. By integrating these approaches, the work aims to improve clinical protocols and ensure optimal care for pregnant women who require emergency oral surgery.